Răspunsuri

2014-11-07T20:34:53+02:00
A+b+c=56
a:b=2 rest 7 adica a=bx2+7
b:c=3 rest 3 adica  b=cx3+3⇒c=(b-3)/3

a+b+c=56
bx2+7 +b+(b-3)/3=56
3xb+(b-3)/3=56-7
3xb+(b-3)/3=49
9xb+b-3=147
10xb=147+3
10xb=150
b=150:10
b=15

a=2xb+7=2x15+7=30+7=37
a=37

c=(b-3)/3=(15-3)/3=12/3=4
c=4


verificam a+b+c=37+15+4=52+4=56
1 1 1
2014-11-07T20:46:23+02:00
A+b+c=56
a:b=2,rest 7=>a=2b+7
b:c=3,rest 3=>c= b:3-3
=> 2b+7 + b + c=56
=> 3b + 7 +c =56
=> 3b+ 7+ b:3-3= 56
=> 3b+b:3-3= 56-7
=> 3b+b:3-3=49
=>3b+b:3=49+3
=>3b+b:3=52
chiar nu imi dau seama cum sa continui